Particle swarm optimization technique (PSO) for dynamic economic dispatch (DED) / Haryanti Kamazahruman - Kamazahruman, Haryanti (2010)
This paper presents application of particle swarm optimization (PSO) technique for assessment of Dynamic Economic Dispatch (DED). Using this method, the best minimum of total generation cost can be obtained. DED is used to determine the optimal schedule of on-line generating output so as to meet the load demand at minimum operating cost under various systems and operating cost over the entire dispatch periods. PSO can solve the problems quickly with high quality solutions and stable convergence characteristics, whereas it is easily implemented evolutionary computation techniques. The DED based PSO techniques is a tested on a 26-bus system containing six generator bus, 20 load bus, and 46 transmission lines.